The Novel lncRNA RP9P Promotes Colorectal Cancer Progression by Modulating miR-133a-3p/FOXQ1 Axis - Jin, Zhichao; Liu, Baoxinzi; Lin, Bofan; Yang, Ran; Wu, Cunen; Xue, Weiwei; Zou, Xi; Qian, Jun (Frontiers in Oncology, 2022)
Background The long non-coding RNA (lncRNA) RP9 pseudogene (RP9P) is a pseudogene-derived lncRNA that has never been reported in cancer, and its function underlying tumorigenesis in colorectal cancer (CRC) remains unknown. Methods RP9P and miR-133a-3p were filtered through bioinformatics analysis. The level of RP9P, miR-133a-3p, and FOXQ1 in CRC cell lines was detected by real-time PCR. Cell Counting Kit-8 and flow cytometric analyses were used to detect cell proliferation and apoptosis, respectively. Interactions between RP9P, miR-133a-3p, and FOXQ1 were confirmed by a dual-luciferase reporter assay. Results RP9P was overexpressed in CRC compared to normal control tissues and cells. Knockdown of RP9P inhibited CRC cell viability. RP9P directly interacted with miR-133a-3p, and miR-133a-3p downregulation abrogated the tumor-suppressing effect of RP9P knockdown. miR-133a-3p directly targeted FOXQ, which was positively regulated by RP9P. RP9P knockdown decreased FOXQ1 expression levels in CRC cells by directly targeting miR-133a-3p via a sponge mechanism. In addition, in vivo experiments in a xenograft model revealed that downregulated RP9P expression inhibited CRC cell tumorigenesis. Conclusion RP9P promotes colorectal cancer progression by regulating the miR-133a-3p/FOXQ1 axis.